ANALISIS DAMPAK PENGKAJIAN TEKNOLOGI PERTANIAN UNGGULAN SPESIFIK LOKASI TERHADAP PRODUKTIVITAS KASUS: BPTP NUSA TENGGARA TIMUR - RITA NUR SUHAETI; EDI BASUNO (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2004)
Impact Analysis of Improved and Location Specific Agricultural Technologieson Productivity, AIAT East Nusa Tenggara Case. By selecting six topics ofimproved research and assessments (R&A), impact analysis on productivity hadbeen carried out in 2002 fiscal year. However, only four out of six topics wereanalyzed, because the other two were still in adaptive level. Application of introducedtechnologies, in fact, resulted in some additional yield. The highest production andproductivity were experienced by R&A of Backyard Farming System, i.e. 569.63percent, then followed by Milk Fish Culture, Bisma Corn Based Agribusiness, BeefCattle Based Agribusiness 482.10 percent, 284.76 percent and 45.0 percent,respectively. Corn Agribusiness gave the largest impact area of 1,365 ha, while itsimpact on production was also excellent, by adding production of 2,319,308.33kg/planting season. Milkfish culture, on the other hand gave the highest income/haper production cycle. Based on relatively high MBCRs, all analyzed topics werefeasible to be developed in the future. Milkfish culture on brackish water was themost profitable business, reflected by the highest MBCR of 14,08. MBCR figures forBackyard Farming, Beef Cattle Agribusiness and Bisma Corn Agribusiness were1.38, 6.24 and 8.61, respectively. Cost and price ratio of each topics were 0.47; 0.21;0.22 and 0.33 for Backyard Farming System, Bisma Corn Agribusiness, Milk FishCulture and Beef Cattle Agribusiness, respectively. The smallest adoption cost perKg product was indicated by Backyard Farming System (Rp 935.85), followed byBisma Corn Agribusiness (Rp 1,028.30) and Milk Fish Culture (Rp 2181.32), whilethe highest was for Beef Cattle Agribusiness (Rp 9,770.03).